Shadow Teacher Program As A Learning Companion For Inclusive ChildrenChildren With Special Needs - Bagus Setiawan (Intelegensia : Jurnal Pendidikan Islam, 2023)
This research aims to discover how the shadow teacher program works as a learning companion for inclusive/special needs children. This research method uses literature study by collecting from various reading sources such as e-books, journals or examination of online literature. The accompanying teacher or also known as the shadow teacher plays a very important role in the classroom because it bridges the gap between the classroom teacher's instructions and student behavior, helps them stay focused, helps them learn, play, interact with their peers, and serves as a conduit of information between parents and classroom teachers to help children teach lessons that are behind schedule.